2004
DOI: 10.1177/0363546503261248
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Tackle Parameters on the Propensity for Injury in International Football

Abstract: The laws of football relating to tackling should be reviewed to provide greater protection from injury by reducing the overall level of risk and, in particular, by protecting players from tackles with the highest propensity for causing injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
1
7

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(73 citation statements)
references
References 13 publications
3
62
1
7
Order By: Relevance
“…Furthermore, we detected a clear tendency in the fact that, the older the studies are the greater the injury risk seems to be however the more recent studies report data that is more similar to our study. This may be due to decreased permissiveness regarding rough play and a stricter application of the playing rules based on the recommendations made in 2004 by the International Soccer Association Board [14]. Regarding injury rates by division, Noya and Sillero, in their study performed in the 1 st and 2 nd division of the Spanish league, reported an injury rate in the 2 nd division of 8.9 injuries/1,000 hours' exposure and in the 1 st division this figure was 9.0 injuries/1,000 hours' exposure to the risk [4].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we detected a clear tendency in the fact that, the older the studies are the greater the injury risk seems to be however the more recent studies report data that is more similar to our study. This may be due to decreased permissiveness regarding rough play and a stricter application of the playing rules based on the recommendations made in 2004 by the International Soccer Association Board [14]. Regarding injury rates by division, Noya and Sillero, in their study performed in the 1 st and 2 nd division of the Spanish league, reported an injury rate in the 2 nd division of 8.9 injuries/1,000 hours' exposure and in the 1 st division this figure was 9.0 injuries/1,000 hours' exposure to the risk [4].…”
Section: Discussionmentioning
confidence: 99%
“…FaCtores média (dp) média (dp) F p , bem como o conhecimento do jogo (5,22) e as habilidades técnicas (28,31) são motivos específicos das competições desportivas. o escape e a família são motivos comuns aos diferentes espectadores desportivos (11,17,28,31) e transversais a outras formas de entretenimento. no entanto, emergem desta investigação dois motivos mais relacionados com o basquetebol.…”
Section: -Rpcd 11 (1)unclassified
“…o sentimento de pertença à equipa e o orgulho na comunidade realçam a importância do reconhecimento social (28) da modalidade e a identificação da equipa enquanto símbolo de uma região (7) . este aspecto, facilmente reconhecível em algumas manifestações desportivas, em particular nos eventos mais mediáticos, como é o caso das grandes competições internacionais de futebol, sugere uma necessidade dos espectadores se sentirem integrados numa comunidade em particular que lhes permita reforçar a sua identidade colectiva (neste caso, através da comunidade do basquetebol).…”
Section: -Rpcd 11 (1)unclassified
See 2 more Smart Citations